Acute pain Factors predictive of post‐operative pain and opioid requirement in multimodal analgesia following knee replacement. (30th October 2015) - Thomazeau, J.; Rouquette, A.; Martinez, V.; Rabuel, C.; Prince, N.; Laplanche, J.L.; Nizard, R.; Bergmann, J.F.; Perrot, S.; Lloret‐Linares, C.
Abstract: Background: Despite the development of multimodal analgesia for postoperative pain management, opioids are still required for effective pain relief after knee arthroplasty. We aimed to identify the determinants of post‐operative pain intensity and post‐operative opioid requirement in this context. Methods: In this observational prospective study, we recorded patient characteristics, pre‐operative pain intensity, anxiety and depression levels, sensitivity and pain thresholds in response to an electrical stimulus, and mu‐opioid receptor (OPRM1) and catechol‐O‐methyltransferase (COMT) single‐nucleotide polymorphisms. Multivariate linear regression models were used to identify predictors of post‐operative pain at rest and opioid requirement. Results: We included 109 patients. Pre‐operative pain at rest ( p  =   0.047), anxiety level ( p  =   0.001) and neuropathic pain symptoms ( p  =   0.030) were independently and positively associated with mean post‐operative pain intensity adjusted for mean post‐operative morphine equivalent dose (MED). Mean post‐operative pain intensity at rest was lower ( p  =   0.006) in patients receiving celecoxib and pregabalin in the post‐operative period, with all other variables constant. Mean post‐operative MED over 5 days was low, but highly variable (78.2 ± 32.1 mg, from 9.9 to 170 mg). Following adjustment for mean post‐operative pain intensity, it was independently negatively correlated with age ( p  =   0.004), and positively correlated with associated paracetamol treatment ( p  =   0.031). No genetic effect was detected in our sample. Conclusions: Our findings suggest that clinicians could use the pre‐operative pain profile, in terms of anxiety levels, neuropathic pain symptoms, and chronic pre‐operative pain intensity, to improve the efficacy of pain management after knee surgery.